2008
DOI: 10.1007/s11064-008-9851-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homovanillic Acid and Prolactin in Huntington’s Disease

Abstract: Dopaminergic activity is expected to be altered in patients with Huntington's disease (HD) and be related to factors like duration and severity of illness or patients' specific symptomatology like dementia, depression, or psychotic features. We assessed plasma homovanillic acid (pHVA) and plasma prolactin (pPRL), two correlates of dopaminergic activity, in 116 subjects with CAG repeats expansion in the HD gene, 26 presymptomatic (18 females) and 90 with overt symptomatology (43 females). Patients were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…the human homologue of the arcuate nucleus in rodents), or the loss of pituitary D 2 receptor expression as described in the R6/2 mice 28 could both underlie the irregular pattern of prolactin secretion in patients with HD. The diminished regularity of prolactin secretion even in our cohort of medication‐free patients with early‐stage HD may also account for the inconsistencies in findings from previous studies on prolactin levels in HD subjects, 7,11,16,17 because the irregular pattern of prolactin release as assessed by a single or a few baseline measurements is unlikely to be properly demonstrated. It remains to be established to what extent the irregular pattern of prolactin secretion in HD could lead to abnormal responses to physiological stimuli of prolactin release, such as stress 8 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…the human homologue of the arcuate nucleus in rodents), or the loss of pituitary D 2 receptor expression as described in the R6/2 mice 28 could both underlie the irregular pattern of prolactin secretion in patients with HD. The diminished regularity of prolactin secretion even in our cohort of medication‐free patients with early‐stage HD may also account for the inconsistencies in findings from previous studies on prolactin levels in HD subjects, 7,11,16,17 because the irregular pattern of prolactin release as assessed by a single or a few baseline measurements is unlikely to be properly demonstrated. It remains to be established to what extent the irregular pattern of prolactin secretion in HD could lead to abnormal responses to physiological stimuli of prolactin release, such as stress 8 .…”
Section: Discussionmentioning
confidence: 61%
“…Compared to thyrotropic axis function, lactotropic axis activity in patients with HD has been investigated more intensively 15 . Nevertheless, as prolactin levels in patients with HD have been reported to be unchanged, 10,16 increased, 11 or even decreased, 17 it still remains unknown whether the lactotropic axis is indeed affected in HD or whether altered prolactin levels are merely a consequence of antidopaminergic medication use in HD. The discordances in findings regarding thyrotropic and lactotropic axes functioning in HD are likely because of the use of a few baseline measurements of hormone levels or long blood sampling intervals which are not adequate to assess either the pulsatile nature of TSH and prolactin secretion or their total daily production rates 18 …”
Section: Introductionmentioning
confidence: 99%
“…The available findings suggest that dopaminergic input from the hypothalamus to the pituitary is not significantly altered in asymptototic HD gene carriers as shown by prolactin and homovanillic acid measures, although differences become apparent post-onset. 42, 43 Previous studies of HD endocrinology have been limited, with findings of reduced HPG axis activity in separate studies examining male 37 and female 38 patients. Interestingly, female testosterone and dehydroepiandrosterone sulphate hormone decline is similar between HD patients and controls, except for those patients with depression, who show significantly lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…measurements vary together or that the peripheral contribution remains relatively stable [17]. Moreover, various authors have found a relationship between the pHVA levels and the severity of certain psychiatric and neurological pathologies [18][19][20][21][22]. Overall, these results suggest that, under controlled conditions, this plasma metabolite may well reflect changes which occur in cerebral dopaminergic activity, especially when measured in response to pharmacological stimuli.…”
Section: Introductionmentioning
confidence: 80%